Accuracy and knowledge in 12-lead ECG placement among nursing students and nurses: a web-based Italian study : Accuracy and knowledge in 12-lead ECG placement - Giannetta, Noemi; Campagna, Giuseppe; Di Muzio, Flavio; Di Simone, Emanuele; Dionisi, Sara; Di Muzio, Marco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Electrocardiogram (ECG) is considered the most used diagnostic tool to identify many cardiological disease and conditions that require the monitoring and recording of heart’s electric activity. The aim of this study is the validation and application of a web-survey, addressed to nursing students and nurses, in order to evaluate the degree of accuracy and the knowledge on the correct positioning of the 12-leads ECG. Methods: The study was a cross-sectional questionnaire-based study. The survey comprised 30 items, mainly multiple-choice questions. The participants were 484 nurses and nursing students. In the study, no exclusion criteria were adopted, but fill in the questionnaire any nurse on duty during the data collection period and/or any nursing student during the data collection period. Statistical analyses were performed using the SAS v. 9.4. In the study, no exclusion criteria were adopted. Results: A total of 484 nursing students and nurses comprising of 149 males (30.79%) and 335 females (69.21%) responded. In full findings showed good psychometric properties and good reliability. The Cronbach’s alpha coefficient for the study is 0.76 (number of items = 17, number of obs= 484). The mean age of responders was 32.01 (Standard deviation (SD) 9.63). A logistic multivariate regression demonstrated significant differences. Conclusions: It is evident from our findings and those from other countries, that more education is required to ensure that mistaken interpretation, misdiagnosis, patient mismanagement and/or inappropriate procedures due to 12 leads ECG misplacement does not occur.